Life Themes and Interpersonal Motivational Systems in the Narrative Self-construction - Veglia, Fabio; Di Fini, Giulia (Frontiers in Psychology, 2017)
What makes unique and unrepeatable individuals is their ability to write their own story attributing meaning, sharing it through narration, giving coherence to the information related to the Interpersonal Motivational Systems, and creating alternative hierarchies to those biologically provided by the genetic code. Through clinical narratives and narrative literature, we can observe the recurrence of specific topics, across time and different cultures. Hence, we wondered whether there are some evolutionary suggestions that guide us in the construction of the narrative-autobiographical contents. In this article we proposed a theoretical-clinical hypothesis about the existence of a biological disposition to identify as fundamental six Life Themes (LTs) that contribute to defining the image of the self and the world: Love, Personal Value, Power, Justice, Truth, and Freedom. Besides the innumerable narratives dependent upon context, there may be many ways of telling stories that, instead, would be reported to these few essential themes. A narrative review of the literature about these concepts follows the systematic explanation of the perspective about the LTs as attractors of meaning. The manuscript considers also the process of co-construction of meanings within the interpersonal relationships and the influences of these on the narratives. In particular, we focused on the importance of episodic and autobiographical memory related to the attachment and significant figures, in the construction of the personal story and the LTs. We also explained the possible clinical implications of the theoretical hypothesis of LTs. Within clinical conversations, the LTs could be expressed rigidly or, otherwise, in a confused way. The lack of narrative integration may lead to the dominance of chaos or rigidity that generates suffering. A better comprehension of the LTs in patients’ narrations could be useful to identify a narrative profile about the areas of greatest suffering related to the idea of self and the world, as well as to construct an adequate care plan.